The Ernesto Cave, northern Italy, as a candidate auxiliary reference section for the definition of the Anthropocene series. (April 2023) - Borsato, Andrea; Fairchild, Ian J; Frisia, Silvia; Wynn, Peter M; Fohlmeister, Jens
Annually laminated stalagmites ER77 and ER78 from Grotta di Ernesto provide an accurate annual record of environmental and anthropogenic signals for the last ~200 years. Two major transitions are recorded in the stalagmites. The first coincides with the year 1840 CE, when a change from porous and impurity-rich-laminae to clean, translucent laminae occurs. This is accompanied by a steady increase in the growth rate, a decrease in fluorescence and a sharp increase in δ 13 C values. These changes concur with the end of the Little Ice Age. The second transition takes place around the year 1960 CE and corresponds with an increase in both annual growth rate and sulfur concentration in stalagmite ER78 at 4.2 mm from the top, and with the deflection point in the 14 C activity curve in stalagmite ER77 at 4.8 mm from the top. This latter is the stratigraphic signal proposed as the primary guide for the definition of the Anthropocene series. The following shift toward depleted δ 34 S–SO4 in stalagmite ER78 suggests that industrial pollution is a major source of sulfur. The interpretation of atmospheric signals (S, δ34 S, 14 C) in the stalagmites is affected by attenuation and time lags and the environmental signals are influenced by soil and ecosystem processes, while other anthropogenic signals (δ 15 N, 239 Pu) are not recorded. For these reasons, the stalagmite record is here proposed as an auxiliary (reference) section rather than a global standard. In summary, Grotta di Ernesto contains one of the best stalagmite records documenting the Anthropocene, and one of only two stalagmite records where the S peak has been measured at high resolution.